KAJIAN RISIKO KESEHATAN MANUSIA TERKAIT KONSUMSI MAKANAN LAUT (SEAFOOD) YANG TERCEMAR LOGAM - Triyoni Purbonegoro (Pusat Penelitian Oseanografi LIPI, 2020)
Consuming contaminated seafood can be potentially harmful for human health, especially for coastal communities. For this reason, a health risk assessment is very important to determine the safe limit for consuming seafood. Several stages in this assessment are; (i) direct comparison with the standard/maximum limit of heavy metal concentration determined by each country or international organization, (ii) determination of the maximum amount of seafood that can be consumed by adults per week, (iii) determination of the Estimated Daily Intake (EDI), and (iv) determination of the Target Hazard Quotient (THQ) of each metal and the Total Hazard Index (HI) for the combined metals.